Medievalism in technology old and new - Fugelso, Karl 1967-; Robinson, Carol L. (Studies in medievalism, 2008)
Medievalism examined in a variety of genres, from fairy tales to today's computer games. As medievalism is refracted through new media, it is often radically transformed. Yet it inevitably retains at least some common denominators with more traditional responses to the middle ages. This latest volume of Studies inMedievalism explores this phenomenon with a special section on computer games, examining digital echoes of the medieval past in subjects ranging from the sovereign ethics of empire in Star Wars to gender identity in on-line role playing. Medievalism in more conventional venues is also addressed, ranging from early French fairy tales to nineteenth-century neo-Byzantine murals. Great innovation and extraordinary continuity are thus juxtaposed not only within each article but also across the volume as a whole, in yet further testimony to the exceptional flexibility and enduring relevance of medievalism. CONTRIBUTORS: ALICIA C. MONTOYA, ALBERT D. PIONKE, GRETCHENKREAHLING MCKAY, CHENE HEADY, BRUCE C. BRASINGTON, STEFANO MENGOZZI, CAROL L. ROBINSON, OLIVER M. TRAXEL, AMY S. KAUFMAN, BRENT MOBERLY, KEVIN MOBERLY, LAURYN S. MAYER